2009
DOI: 10.1007/s00420-009-0450-5
|View full text |Cite
|
Sign up to set email alerts
|

Skin temperature in the dorsal hand of office workers and severity of upper extremity musculoskeletal disorders

Abstract: Reduced dorsal hand skin temperature after acclimating to an ambient temperature of 18-22 degrees C in those with more severe UEMSDs may reflect an underlying dysfunctional sympathetic nervous system. Further testing in epidemiological cohorts would be desirable to evaluate the generalizability and feasibility of this physiological measurement for UEMSD severity in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…Ha sido ampliamente demostrado que el ejercicio físico dinámico produce cambios en la temperatura cutánea 7,8,14 y que el sistema nervioso simpático es el mayor determinante de la temperatura cutánea 15 , no hay conocimiento previo acerca de los efectos térmicos cutáneos asociados con la simple variación de la postura ortostática. Se puede suponer que el aumento en el metabolismo y el calor producido en los músculos involucrados en el control del equilibrio y la postura puede ser transferido a las capas cutáneas 11 .…”
Section: Discussionunclassified
“…Ha sido ampliamente demostrado que el ejercicio físico dinámico produce cambios en la temperatura cutánea 7,8,14 y que el sistema nervioso simpático es el mayor determinante de la temperatura cutánea 15 , no hay conocimiento previo acerca de los efectos térmicos cutáneos asociados con la simple variación de la postura ortostática. Se puede suponer que el aumento en el metabolismo y el calor producido en los músculos involucrados en el control del equilibrio y la postura puede ser transferido a las capas cutáneas 11 .…”
Section: Discussionunclassified
“…Vasoconstriction of the radial artery and lack of a vasodilatory response to exercise were found in patients (Pritchard et al 1999). Further, changes in skin temperature determined by thermography (i.e., far infrared images) showed reduced temperature in the afflicted region among patients with forearm pain, possibly reflecting sympathetic dysfunction (Sharma et al 1997;Gold et al 2009). …”
Section: Autonomic Aberrations In Chronic Neck-shoulder Pain: Recent mentioning
confidence: 98%
“…However it has been reported that reduced dorsal may reflect an underlying dysfunctional sympathetic nervous system [2]. In the lower limb there is a body 48 of evidence that suggests some patellofemoral pain…”
mentioning
confidence: 99%